Answer:
= 2
where:
is the sum of the terms in the first sequence, and
is the sum of the terms in the second sequence.
Explanation:
The two sequences are arithmetic progression.
From the first sequence,
first term, a = 2
common difference, d = 2
number of terms, n = 5
From the second sequence,
first term, a = 1
common difference, d = 1
number of terms, n = 5
The sum of terms of an arithmetic progression is given as;
=
[2a + (n - 1) x d]
⇒ Let the sum of the first sequence be represented by
, so that;
=
[2(2) + (5 - 1) x 2]
=
[4 + 8]
=
x 12
= 30
⇒ Let the sum of the second sequence be represented by
, so that;
=
[2(1) + (5 - 1) x 1]
=
[2 + 4]
= 15
Thus, the statement that would correctly describe the relationship between the sequences is;
= 2
where:
is the sum of the terms in the first sequence, and
is the sum of the terms in the second sequence.